The Future of Cervical Cancer Screening - Goldstein A; Gersh M; Skovronsky G; Moss C (Dove Medical Press, 2024)
Amelia Goldstein,1 Mallory Gersh,2 Gabriela Skovronsky,3 Chailee Moss4 1Duke University, Durham, NC, USA; 2Wake Forest University, Winston-Salem, NC, USA; 3University of Pennsylvania, Philadelphia, PA, USA; 4George Washington University School of Medicine and Health Sciences, Washington, D.C., USACorrespondence: Amelia Goldstein, Clinical Research, Gynecologic Cancers Research Foundation, 25 W Houston St, Apt 3D, New York, NY, USA, Tel +1 410 599 3484, Email amelia.goldstein@gmail.comPurpose: Cervical cancer remains a significant health concern, particularly in developing countries, where it is a leading cause of cancer-related deaths among women. Innovative technologies have emerged to improve the efficiency, cost-effectiveness, and sensitivity of cervical cancer screening and treatment methods. This study aims to explore the various approaches for the detection and treatment of human papillomavirus (HPV), cervical dysplasia (CD), and cervical cancer, highlighting new technologies and updated screening strategies in developing areas.Patients and Methods: A comprehensive literature search was conducted using PubMed to identify relevant publications on the subject of cervical cancer screening and HPV detection.Results: HPV infection and cervical cancer continue to pose significant global health challenges. Emerging technologies such as rapid, low-cost HPV testing combined with high-resolution digital colposcopy and artificial intelligence interpretation hold promise for efficient and sensitive screening. Advancements in HPV vaccine distribution, high-risk HPV screening, DNA methylation assays, dual-stain cytology, lab-on-chip assays, and deep learning technologies offer new avenues for improved detection and risk stratification.Research and innovations in detection and treatment methods are crucial for reducing the burden of these diseases worldwide.Conclusion: Screening for HPV and CD plays a pivotal role in reducing the risk of cervical cancer-related mortality. The development of novel technologies, along with efforts to enhance global health equity and integrate cervical cancer prevention with HIV screening and treatment programs, represent critical steps toward achieving comprehensive cervical cancer screening on a global scale.Keywords: human papillomavirus, cervical automated visual evaluation, digital colposcope, HPV self-swab